2011
DOI: 10.1007/128_2011_195
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Predictions from Ab Initio Molecular Dynamics Simulations

Abstract: In this review we present the techniques of ab initio molecular dynamics simulation improved to its current stage where the analysis of existing processes and the prediction of further chemical features and real-world processes are feasible. For this reason we describe the relevant developments in ab initio molecular dynamics leading to this stage. Among them, parallel implementations, different basis set functions, density functionals, and van der Waals corrections are reported. The chemical features accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 225 publications
(248 reference statements)
1
104
0
Order By: Relevance
“…This leads to finite energies, but it does neither prevent the Coulombic interaction of charged species with their own periodic images, nor the interaction of the charged species with the background charge, leading ultimately to problems when calculating absolute energies. 81,82 The interaction energy of a [C 1 C 1 Im] + ion in flat conformation on the (101) anatase surface for systematically increased supercell size of almost quadratic shape along with the corresponding charge transfer between surface and ion is depicted in Figure 2 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Page 11 of 38…”
Section: Supercell Size Background Chargementioning
confidence: 98%
“…This leads to finite energies, but it does neither prevent the Coulombic interaction of charged species with their own periodic images, nor the interaction of the charged species with the background charge, leading ultimately to problems when calculating absolute energies. 81,82 The interaction energy of a [C 1 C 1 Im] + ion in flat conformation on the (101) anatase surface for systematically increased supercell size of almost quadratic shape along with the corresponding charge transfer between surface and ion is depicted in Figure 2 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Page 11 of 38…”
Section: Supercell Size Background Chargementioning
confidence: 98%
“…The traditional calculation of normal mode-dependent dipole and polarizability derivatives to simulate infrared and Raman spectra in the static approach or frequency domain is replaced by Fourier transforms of the dipole and polarizability correlation functions in the time domain dynamics simulations. 26 Because no approximations are invoked to approximate the shape of the potential energy landscape in AIMD simulations, vibrational spectra evaluated from these simulations are inherently more physical than their harmonic analogues that are evaluated at a minimum. 30 In principle, with adequate statistical sampling and in the absence of significant mode coupling leading to combination bands and Fermi resonances, the only assumptions stem from the level of the underlying electronic structure approach used to treat the molecular system.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In particular, instantaneous polarization effects captured by maximally localized Wannier functions showed that the dipole moment of AIMD exhibited much larger variation than a fixed dipole typically used in empirical potentials [65][66][67]. The discrepancies evidenced by this pioneering simulation laid the foundation for many of the theoretical issues that have been revisited in numerous publications [31,64,65,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. There continues to be an ongoing lively debate on the molecular origins of these discrepancies.…”
Section: (A) Bulk Watermentioning
confidence: 94%